Removal of spermatozoa with externalized phosphatidylserine from sperm preparation in human assisted medical procreation: effects on viability, motility and mitochondrial membrane potential - de Agostini Ariane; Chardonnens Didier; Lucas Hervé; de Vantéry Arrighi Corinne (BMC, 2009)
Abstract Background Externalization of phosphatidylserine (EPS) occurs in apoptotic-like spermatozoa and could be used to remove them from sperm preparations to enhance sperm quality for assisted medical procreation. We first characterized EPS in sperms from infertile patients in terms of frequency of EPS spermatozoa as well as localization of phosphatidylserine (PS) on spermatozoa. Subsequently, we determined the impact of depleting EPS spermatozoa on sperm quality. Methods EPS were visualized by fluorescently-labeled annexin V binding assay. Double staining with annexin V and Hoechst differentiates apoptotic from necrotic spermatozoa. We used magnetic-activated cell sorting using annexin V-conjugated microbeads (MACS-ANMB) technique to remove EPS spermatozoa from sperm prepared by density gradient centrifugation (DGC). The impact of this technique on sperm quality was evaluated by measuring progressive motility, viability, and the integrity of the mitochondrial membrane potential (MMP) by Rhodamine 123. Results Mean percentages of EPS spermatozoa were 14% in DGC sperm. Four subpopulations of spermatozoa were identified: 70% alive, 3% early apoptotic, 16% necrotic and 11% late apoptotic or necrotic. PS were localized on head and/or midpiece or on the whole spermatozoa. MACS efficiently eliminates EPS spermatozoa. MACS combined with DGC allows a mean reduction of 70% in EPS and of 60% in MMP-disrupted spermatozoa with a mean increase of 50% in sperm survival at 24 h. Conclusion Human ejaculates contain EPS spermatozoa which can mostly be eliminated by DGC plus MACS resulting in improved sperm long term viability, motility and MMP integrity. EPS may be used as an indicator of sperm quality and removal of EPS spermatozoa may enhance fertility potential in assisted medical procreation.